2011
DOI: 10.1073/pnas.1101934108
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Probing osmolyte participation in the unfolding transition state of a protein

Abstract: Understanding the molecular mechanisms of osmolyte protection in protein stability has proved to be challenging. In particular, little is known about the role of osmolytes in the structure of the unfolding transition state of a protein, the main determinant of its dynamics. We have developed an experimental protocol to directly probe the transition state of a protein in a range of osmolyte environments. We use an atomic force microscope in force-clamp mode to apply mechanical forces to the protein I27 and obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Such a discrepancy can stem from the different reaction coordinate probed in the force spectroscopy experiments, where the end-to-end length of the protein is recorded over time, and also from the different molecular mechanisms underlying the mechanical unfolding process. The accumulated evidence through both experiments and molecular dynamics simulations demonstrates that water insertion within the structural mechanical clamp is a key and necessary step to trigger mechanical unfolding (30,37,41,64,65). Indeed, recent experiments have shown that the value of ⌬x measured for protein unfolding under force is determined by the bridging length of solvent molecules at the transition state structure of the reaction (30).…”
Section: Discussionmentioning
confidence: 99%
“…Such a discrepancy can stem from the different reaction coordinate probed in the force spectroscopy experiments, where the end-to-end length of the protein is recorded over time, and also from the different molecular mechanisms underlying the mechanical unfolding process. The accumulated evidence through both experiments and molecular dynamics simulations demonstrates that water insertion within the structural mechanical clamp is a key and necessary step to trigger mechanical unfolding (30,37,41,64,65). Indeed, recent experiments have shown that the value of ⌬x measured for protein unfolding under force is determined by the bridging length of solvent molecules at the transition state structure of the reaction (30).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, because osmolyte molecules are larger than water molecules, the small osmolytes were reported to increase the unfolding distance of proteins by amounts that correlate with their molecular size. It should be noted, however, that larger osmolytes such as sorbitol and sucrose were instead found to leave the unfolding distance of I27 unchanged, indicating their inability to partake in solvent bridging (6).…”
Section: Introductionmentioning
confidence: 96%
“…A previous SMFS study of mechanical unfolding of protein ubiquitin reported that the presence of glycerol as a cosolvent in aqueous solution leads to an increase of the protein's unfolding distance (4). Other SMFS studies reported that glycerol (5), ethylene glycol, and propylene glycol (6) increase the unfolding distance of the I27 titin module of the human muscle. Based on the Ansatz that the unfolding distance of proteins may be determined by the bridging length of solvent molecules at the unfolding transition state (7,8), the mentioned SMFS studies concluded that small osmolyte molecules bridge the critical b-strands of proteins under mechanical tension, leaving their distinct signature on their unfolding distance.…”
Section: Introductionmentioning
confidence: 99%
“…All the pKa values were obtained by pH measurement of a solution of 4 wt% of the desired compound with 40 mL volume using a pHmeter. Numbers in parentheses are collected from PubChem [27][28][29]; molecular size is obtained from [30]; * estimated value.…”
Section: Understanding the Adsorption Mechanismmentioning
confidence: 99%